Risk mitigation guideline for click-and-mortar VS pure play companies / Nik Faizah Nik Rahmat - Nik Rahmat, Nik Faizah (2005)
E-retailing provides a relatively new way of marketing, selling, paying and the delivery of goods over the Internet. A guideline suggested here to be followed to mitigate risks of running a web store consist of five stages; i) identifying risk factor and risk type, ii) analyzing risk scenario, iii) predicting the consequences of risk occurring, iv) planning for proper risk mitigation mechanism and v) assigning the right people to manage the risk. Results from this study also indicated that risks faced by click-andmortar and pure play e-tailers are similar in terms of customer and internet risks but very different in terms of business risks since click-and-mortar e-tailers usually have a higher budget at their disposal to spend in handling online business risks. In conclusion, businesses that conduct their transactions online will have to be ready to face problems that may not arise in running conventional stores. These risks, if left without proper handling, might lead to the downfall of e-tailers.